Can market selection reduce anomalous behaviour in games? - Zhou, Xiaoyu; Choo, Lawrence (European Economic Review, 2022)
We use an experiment to study whether market selection can reduce anomalous behaviour in games. In different treatments, we employ two alternative mechanisms, the random mechanism and the auction mechanism, to allocate the participation rights to the red hat puzzle game, a well-known logical reasoning problem. Compared to the random mechanism, the auction mechanism significantly reduces deviations from the equilibrium play in the red hat puzzle game. Our findings show that under carefully designed incentives, market competition can indeed reduce anomalous behaviour in games.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Market competition; Market selection; Auctions; Bounded-rationality; Red hat puzzle

Rice Farming and the Origins of Cooperative Behaviour - Zhou, Xiaoyu; Alysandratos, Theodore; Naef, Michael (The Economic Journal, 2023)
This paper provides novel evidence for links between historic farming practices and current norms of cooperative behaviour. We hypothesise that the cooperation required in wetland rice farming gives rise to strong cultural norms of cooperativeness. We compare participants from prefecture cities that predominately practice wetland rice cultivation to those from non-rice regions. A public goods game with and without punishment is the main measure for cooperative behaviour. Results indicate a strong and robust positive effect of wetland rice farming on cooperative behaviour and pro-social punishment. Complementary, consistent evidence from a natural field experiment and a survey further enriches our data.
CRIS-Team WoS Importer:2023-05-19

Size Matters! Only Big Threats Encourage Cooperation - Zhou, Xiaoyu; Hartig, Bjoern (2021)
Subjects play a repeated stranger-matching prisoners’ dilemma game with opt-in fee for both players framed as escrow account payments. After a game, all fees can be consensually returned or unilaterally destroyed. With low fees, cooperation breaks down at a similar rate as without fees. However, cooperation rates remain stable with high fees. The effect is primarily driven by cooperators remaining active and willing to cooperate, not by defectors drop- ping out or turning to cooperation. Destruction of the fees is rare and never triggered by defectors, but occurs slightly more with high fees. Fees have no effect on participation rates.
Keywords: Prisoners’ Dilemma; Punishment; Revenge; Trust